Perseus 6.0: Towards a Next Generation Reading Environment for Born-Digital Editions and Corpora - Crane, Gregory; Babeu, Alison; Cerrato, Lisa; Shamsian, Farnoosh; Tauber, Tames; Wegner, Jacob (IEEE/ACM Joint Conference on Digital Libraries (Online), 2023)
The Beyond Translation Project has developed a new reading environment for multilingual sources to address several challenges. First, we wanted to create a new digital library system for the Perseus Digital Library that could support new classes of borndigital data about historical sources. Second, we wanted to assess the feasibility of integrating openly licensed data of different types from multiple, independent projects from various countries. Third, we wanted to create a reading environment in which audiences use a growing range of annotations to go from translations into sources composed in languages that they do not know. We report here on Perseus 6.0, the initial release of work by Beyond Translation and the first iteration of the sixth generation system for the Perseus Digital Library.